2010
DOI: 10.1186/1471-2474-11-179
|View full text |Cite
|
Sign up to set email alerts
|

A treatment applying a biomechanical device to the feet of patients with knee osteoarthritis results in reduced pain and improved function: a prospective controlled study

Abstract: BackgroundThis study examined the effect of treatment with a novel biomechanical device on the level of pain and function in patients with knee OA.MethodsPatients with bilateral knee OA were enrolled to active and control groups. Patients were evaluated at baseline, at 4 weeks and at the 8-week endpoint. A novel biomechanical device was individually calibrated to patients from the active group. Patients from the control group received an identical foot-worn platform without the biomechanical elements. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 33 publications
4
52
0
Order By: Relevance
“…Biomechanical interventions focusing on foot center of pressure (COP) manipulation, agility, and perturbation training have been suggested for the treatment of knee OA (Bar-Ziv et al, 2010; Elbaz et al, 2010;Fitzgerald et al, 2002;Hurley and Scott, 1998;Thorstensson et al, 2007). Such interventions were reported to facilitate superior levels of functional activity, to reduce pain, and to influence spatiotemporal parameters during gait (Bar-Ziv et al, 2010;Elbaz et al, 2010;Erhart et al, 2010;Fitzgerald et al, 2002;Roddy et al, 2005;Thorstensson et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Biomechanical interventions focusing on foot center of pressure (COP) manipulation, agility, and perturbation training have been suggested for the treatment of knee OA (Bar-Ziv et al, 2010; Elbaz et al, 2010;Fitzgerald et al, 2002;Hurley and Scott, 1998;Thorstensson et al, 2007). Such interventions were reported to facilitate superior levels of functional activity, to reduce pain, and to influence spatiotemporal parameters during gait (Bar-Ziv et al, 2010;Elbaz et al, 2010;Erhart et al, 2010;Fitzgerald et al, 2002;Roddy et al, 2005;Thorstensson et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Bar-Ziv et al, in a prospective, sham control study that evaluated the effect of this therapy in patients suffering from knee OA, demonstrated an improvement in function and a reduction in pain following eight weeks of therapy in the experimental group, without similar changes in the level of pain and function in the control group [13]. Elbaz et al in a study on patients with knee OA, showed that three months of therapy with the biomechanical device led to significant improvement in function, pain and gait parameters [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta-analysis from 2009, which reviewed more than 4,000 articles, concluded that there was insufficient evidence to suggest that exercise therapy was an effective shortterm management approach for reducing pain levels, improving joint function and QoL [11]. A novel biomechanical device (Apos System, APOS-Medical and Sports Technologies Ltd.) was recently introduces as a non-invasive therapy for different musculoskeletal problems [12][13][14][15]. Haim et al showed that by using this biomechanical intervention for symptomatic bilateral knee OA, walking velocity and functional activity were increased while knee adduction moment and pain were reduced [16].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have related meniscus injuries with the development of knee OA [6,26,28]. The implemented therapy of this study has been shown to have a positive therapeutic effect on the gait pattern, physical function and pain of patients with knee OA [3,11,17,20]. Therefore, it can be suggested that this treatment modality has the potential to be beneficial in two timeframes: the short-term rehabilitation of patients with meniscal tears and the longterm treatment for knee OA.…”
Section: Discussionmentioning
confidence: 99%